PENGEMBANGAN MANAJEMEN BERBASIS DATA (SMART-PKBM) UNTUK MENINGKATKAN KUALITAS PELAYANAN PUBLIK PADA PKBM DI KOTA SALATIGA - Lestariningtyas, Lestariningtyas; Kusumaningsih, Widya; Ginting, Rosalina B.R. (Jurnal Manajemen dan Profesional, 2024)
In line with the rapid development of information technology, PKBM is faced with an urgent need to optimize information management in order to increase efficiency, accountability and quality of educational services provided. One form of non-formal education is equal education packages A, B and C at the Teaching and Learning Activity Center (PKBM). Based on observations and interviews conducted with PKBM in Salatiga, it can be seen that all of the twelve PKBMs still use conventional methods in the process of storing, processing and conveying information that occurs at PKBM regarding the storage of student data archives. This research is a type of Research and Development (R&D) research using a development model, namely the ADDIE development model. Development of Data-Based Management to Improve the Quality of Public Services at PKBM in Salatiga City is effective in improving the Quality of Public Services. The average value of improving the quality of public services at PKBM in Salatiga City is 85%, which shows the effectiveness of this system in improving services at PKBM. Keywords: Public service, PKBM, R&D, ADDIE.